Simulation-Based Evaluation of Ease of Wayfinding Using Digital Human and As-Is Environment Models - Maruyama, Tsubasa; Kanai, Satoshi; Date, Hiroaki; Tada, Mitsunori (ISPRS international journal of geo-information, 2017)
As recommended by the international standards, ISO 21542, ease of wayfinding must be ensured by installing signage at all key decision points on walkways such as forks because signage greatly influences the way in which people unfamiliar with an environment navigate through it. Therefore, we aimed to develop a new system for evaluating the ease of wayfinding, which could detect spots that cause disorientation, i.e., “disorientation spots”, based on simulated three-dimensional (3D) interactions between wayfinding behaviors and signage location, visibility, legibility, noticeability, and continuity. First, an environment model reflecting detailed 3D geometry and textures of the environment, i.e., “as-is environment model”, is generated automatically using 3D laser-scanning and structure-from-motion (SfM). Then, a set of signage entities is created by the user. Thereafter, a 3D wayfinding simulation is performed in the as-is environment model using a digital human model (DHM), and disorientation spots are detected. The proposed system was tested in a virtual maze and a real two-story indoor environment. It was further validated through a comparison of the disorientation spots detected by the simulation with those of six young subjects. The comparison results revealed that the proposed system could detect disorientation spots, where the subjects lost their way, in the test environment.